Population of vector and tungro disease incidence at dosage of nitrogen fertilizer in rice field - Gunawan, Achmad; Purwono; Lubis, Iskandar; Widiarta, I Nyoman; Suwitono, Bayu (Jurnal AGRO, 2025)
One of the biotic threats that can reduce rice yield is tungro disease. This disease is spread with green leafhopper (Nephotettix virescens) vector. The population density of leafhoppers is one of the factors contributing to the increased incidence of tungro. Excessive nitrogen used in crop cultivation, especially rice, has been known to impact the population dynamics of insect pests. This study aims to determine the population development of green leafhoppers at different nitrogen doses. The study was conducted at the Muara Experimental Field, Bogor. The experimental treatment used three rice varieties representing susceptible varieties, resistant to green leafhoppers and resistant to tungro virus (Ciherang, IR64 and Inpari 36 Lanrang) and four levels of fertilization doses (without additional urea, Urea 250 kg ha-1, 350 kg ha-1 and 500 kg ha-1). The experiment used Split Plot design with three replication. The insect population in the field was found at the beginning of the observation and the peak of insect population density occurred at 6 WAP observationsVariety has a significant effect on insect vector population density and plant growth and yield in the field. The population density of green leafhoppers was higher in the Ciherang and IR 64 varieties than in the Inpari 36 Lanrang variety. Fertilization doses had no significant effect on the population of green leafhopper insects in the field except in the nymph phase in fertilization without the addition of urea and had no effect on growth and yield except on the number of tillers. The combination of resistant varieties and fertilization without the addition of urea reduced the population density of green.   ABSTRAK Cekaman biotik yang dapat menurunkan hasil padi salah satunya penyakit tungro. Penyakit ini disebarkan oleh vektor wereng hijau (Nephotettix virescens). Kepadatan populasi wereng menjadi salah satu faktor penyebab meningkatnya keberadaan penyakit tungro. Penggunaan nitrogen yang berlebihan dalam budidaya tanaman, terutama padi, telah diketahui berdampak pada dinamika populasi serangga hama. Penelitian ini bertujuan untuk mengetahui perkembangan populasi wereng hijau pada pemberian dosis nitrogen berbeda.Penelitian dilakukan di Kebun Percobaan Muara, Bogor. Perlakuan percobaan mengunakan tiga varietas padi yang mewakili varietas rentan, tahan wereng hijau dan tahan virus tungro (Ciherang, IR64 dan Inpari 36 Lanrang) dan lima taraf dosis pemupukan (tanpa tambahan pupuk urea, Pupuk Urea 250 kg ha-1, 300 kg ha-1 dan 500 kg ha-1). Percobaan mengunakan rancanngan Split Plot dalam RAK dengan tiga kali ulangan. Populasi serangga di lapangan ditemukan diawal pengamatan dan puncak kepadatan populasi serangga terjadi pada pengamatan 6 MST. Varietas berpengaruh nyata terhadap kepadatan populasi serangga vektor, pertumbuhan dan hasil tanaman di lapangan. Kepadatan populasi wereng hijau lebih tinggi pada pertanaman varietas Ciherang dan IR 64 dibandingkan pada varietas Inpari 36 Lanrang. Dosis pemupukan tidak berpengaruh nyata terhadap populasi serangga wereng hijau di lapangan kecuali pada fase nimfa pada pemupukan tanpa penambahan urea dan tidak berpengaruh terhadap pertumbuhan dan hasil kecuali pada jumlah anakan. Kombinasi varietas tahan dan pemupukan tanpa penambahan urea mengurangi kepadatan populasi wereng hijau menyebarkan virus tungro.   Kata kunci: Populasi, pupuk nitrogen, wereng hijau